Utility of Immunohistochemistry With Antibodies to SS18-SSX Chimeric Proteins and C-Terminus of SSX Protein for Synovial Sarcoma Differential Diagnosis - Lasota, Jerzy; Chłopek, Małgorzata; Kaczorowski, Maciej; Natálie, Klubíčková; Ryś, Janusz; Kopczyński, Janusz; Sulaieva, Oksana; Michal, Michael; Kruczak, Anna; Harazin-Lechowska, Agnieszka; Szczepaniak, Magdalena; Koshyk, Olena; et al. (The American journal of surgical pathology, 2024)
Synovial sarcoma is a relatively common soft tissue tumor characterized by highly specific t(X;18)(p11;q11) translocation resulting in the fusion of SS18 with members of SSX gene family. Typically, detection of SS18 locus rearrangement by fluorescence in situ hybridization or SS18 :: SSX fusion transcripts confirms the diagnosis. More recently, immunohistochemistry (IHC) for SS18-SSX chimeric protein (E9X9V) and C-terminus of SSX (E5A2C) showed high specificity and sensitivity for synovial sarcoma. This study screened a cohort of >1000 soft tissue and melanocytic tumors using IHC and E9X9V and E5A2C antibodies. Three percent (6/212) of synovial sarcomas were either negative for SS18-SSX or had scattered positive tumor cells (n=1). In these cases, targeted RNA next-generation sequencing detected variants of SS18 :: SSX chimeric transcripts. DNA methylation profiles of 2 such tumors matched with synovial sarcoma. A few nonsynovial sarcoma tumors (n=6) revealed either focal SS18-SSX positivity (n=1) or scattered positive tumor cells. However, targeted RNA next-generation sequencing failed to detect SS18 :: SSX transcripts in these cases. The nature of this immunopositivity remains elusive and may require single cell sequencing studies. All synovial sarcomas showed positive SSX IHC. However, a mosaic staining pattern or focal loss of expression was noticed in a few cases. Strong and diffuse SSX immunoreactivity was also seen in epithelioid sclerosing osteosarcoma harboring EWSR1 :: SSX1 fusion, while several sarcomas and melanocytic tumors including cellular blue nevus (5/7, 71%) revealed focal to diffuse, mostly weak to intermediate SSX staining. The SS18-SSX and SSX IHC is a useful tool for synovial sarcoma differential diagnosis, but unusual immunophenotype should trigger molecular genetic testing.
Keywords: Soft Tissue Neoplasms; nádory měkkých tkání; In Situ Hybridization, Fluorescence; Recombinant Fusion Proteins; Diagnosis, Differential; Oncogene Proteins, Fusion; lidé; imunohistochemie; synoviom; RNA; fúzní onkogenní proteiny; Sarcoma, Synovial; Immunohistochemistry; rekombinantní fúzní proteiny; hybridizace in situ fluorescenční; Humans; diferenciální diagnóza